The Mathematica Kernel Programming Codes Designed for Implementing Block Milne's Device - Oghonyon, J G; Omoregbe, N A; Bishop, S A (Lecture notes in engineering and computer science, 2019)
In this article, we propose the Mathematica kernel programming codes designed for implementing block Milne's device employing an expounded trigonometrically fitted method. Block Milne's device is an extraction of Adam's family constructed via expounded trigonometrically fitted method. We execute the Mathematica kernel programming codes of block Milne's device in a block by block mode. This proficiencies of scientific computing have great advantages of easy computation, speed, faster convergence and accuracy. Other numerical gains of block Milne's device includes; changing the step-size, deciding the convergence criteria and control errors. Additionally, the Mathematica kernel programming codes for implementing block Milne's device is performed on some special problems to demonstrate the accuracy and efficiency.